Performance Analysis Of Information System/Information Technology using COBIT 4.1 - Dian Elvana Purnama; Agustinus Fritz Wijaya; Ariya Dwika Cahyono (Journal of Information System and Informatics, 2020)
The application of information technology to organizations is being promoted. Performance measurement of Information Systems / Information Technology (SI / IT) in companies needs special attention, because the procurement consciousness of IS / IT is expected to provide great benefits to the company. This study aims to determine the extent of the performance of information systems that have been applied to PT Global Infotech Solution and provide recommendations for improved governance after knowing the Gap between current governance and expected management in accordance with the framework used. The framework used in this study is COBIT version 4.1 specifically on Domain Plan and Organize. The technique of data collection is done by observation and interviews with predetermined sources in accordance with the domain and Control Objective used. At this stage, an assessment based on maturity level is carried out to measure the level of IT maturity in the chosen domain based on the results of interviews and observations made previously, then a gap analysis is performed to determine the gap between the results of the current maturity level and the target maturity level going forward. The results of this study are to determine the level of maturity (maturity level) in special companies in the PO Domain, which is at level 2.7 which means it has been measured and integrated between the processes that take place. And GAP analysis between conditions. expected with current conditions an average of 1.3.